2011
DOI: 10.3233/jad-2011-102136
|View full text |Cite
|
Sign up to set email alerts
|

Cotinine Reduces Amyloid-β Aggregation and Improves Memory in Alzheimer's Disease Mice

Abstract: Alzheimer's disease (AD) affects millions of people world-wide and new effective and safe therapies are needed. Cotinine, the main metabolite of nicotine, has a long half-life and does not have cardiovascular or addictive side effects in humans. We studied the effect of cotinine on amyloid-β (Aβ) aggregation as well as addressed its impact on working and reference memories. Cotinine reduced Aβ deposition, improved working and reference memories, and inhibited Aβ oligomerization in the brains of transgenic (Tg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 83 publications
(121 reference statements)
3
100
0
Order By: Relevance
“…Furthermore, it was reported that nicotine can decrease amyloid precursor protein (APP) secretion in animal models 10,11 , inhibit acquisition of b-sheet conformation by Ab peptide 12 , diminish its aggregation 13 , reduce bamyloidosis 14 and prevent memory impairment 15 . In fact, cotinine, the main metabolite of nicotine, is able to reduce Ab deposition by inhibiting its oligomerization and decrease memory impairment in transgenic AD mice 16 . Moreover, some studies have found that smoking is able to reduce Ab42 levels both in control and AD patients 17 .…”
mentioning
confidence: 99%
“…Furthermore, it was reported that nicotine can decrease amyloid precursor protein (APP) secretion in animal models 10,11 , inhibit acquisition of b-sheet conformation by Ab peptide 12 , diminish its aggregation 13 , reduce bamyloidosis 14 and prevent memory impairment 15 . In fact, cotinine, the main metabolite of nicotine, is able to reduce Ab deposition by inhibiting its oligomerization and decrease memory impairment in transgenic AD mice 16 . Moreover, some studies have found that smoking is able to reduce Ab42 levels both in control and AD patients 17 .…”
mentioning
confidence: 99%
“…It has been shown that cotinine binds to Aβ with high affinity (K a =10 nM) [10] inhibiting its aggregation into fibrils in vitro [11]. A previous study also showed that cotinine reduced oligomeric Aβ levels in vivo [2]. However, whether the reduction in Aβ 1−42 oligomers was induced by a decrease in the peptide oligomerization it was not defined.…”
Section: Discussionmentioning
confidence: 98%
“…Previous evidence obtained in vivo [2] and this in vitro evidence suggests that cotinine has the potential to be a new pharmacological therapy against AD. .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations